PERANAN KOPERASI, DALAM PENGEMBANGAN USAHA MIKRO, KECIL DAN MENENGAH (UMKM) UNTUK MENDUKUNG PERMODALAN DAN MENGURANGI PENGANGGURAN DI KECAMATAN TRIMURJO - Chamdini Puri (Jurnal At Taajir, 2021)
Efforts made for economic development through micro, small and medium enterprisesbasically require approprite and strategic steps. The presence of these UMKM provides aglimpse of awaited hope to build the economy, reduce poverty and unemployment. However,behind these strengths there are problems that become obstacles for UMKM to continue theirrole, namely the availability of capital and difficulty in accessing capital to financialinstitutions or cooperatives as providers of business capital loans. So far, there are still manyUMKM players who are forced to lay off their businesses even though there is not enoughcapital to continue their business. And also there are still many cooperative units that do notdisburse loans to UMKM related to problems faced by cooperative institutions and so areafraid of defaults when UMKM take place. This study aims to reveal various factors that causethe role of cooperatives to be not optimal in helping the development of UMKM through theprovision of venture capital. The method used in this research is quantitative descriptivemethod by using cross tabulation between variables which is the researcher's observation. Theresults showed that the role of cooperatives was still very low in empowering the capital ofUMKM. There are many factors that lead to the low role of cooperatives in the progress ofUMKM in Trimurjo District, namely, 1) there is still a small number of cooperatives comparedto the number of UMKM, 2) there is still a low level of public understanding of the importanceof cooperating, 3) low capacity of cooperative human resources both in terms of understandingof benefits and in terms of understanding. Managing manaagement, 4) lack of trust from thecooperative towards UMKM actors. These various factors have caused very few UMKM actorsto join and collaborate in cooperative forums so that cooperatives still have a low role inhelping the development of UMKM through business capital providers.